Women and Educational Leadership - Kristen Angela Clarke (University of Windsor, 2012)
Women and Educational Leadership provides insight into five leadership frameworks that women employ in the role of principal and superintendent and how these frameworks inform the concept of diverse collective leadership. Grogan and Shakeshaft use their expertise in the field and over 20 years of research to examine the topic. The authors contend that an examination of how women lead can result in a deeper understanding of an educational leadership concept that reflects diverse perspectives and that involves a community as opposed to a single leader.